Docência e formação continuada de professores na Educação Infantil - de Marco, Marilete Terezinha [UNESP]; de Lima, Elieuza Aparecida [UNESP] (My University, 2017)
Among the Early Childhood Education goals, we highlight the whole development of the little child, whose effectiveness happens by means of pedagogical practices that are motivators of knowledge appropriation culturally elaborated. Aiming to reach the maxima possibilities of Early Childhood humanization, the little children teachers require a solid initial education and a permanent education to provide improvement, deepening and professional updating. As objective of this research, the teaching and continuous teacher education sets the performance of bibliographical and field actions, such as class observation, interview and study groups with the partner teachers of an Early Childhood Public School, located in the west region of Paraná State.
Teaching and continuous teacher education for the Early Childhood Education
Keywords: Continuous Teacher Education; Early Childhood Education; Teaching